2011
DOI: 10.1111/j.1601-0825.2011.01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of hyaluronic acid on the anticandidal activities of lysozyme and the peroxidase system

Abstract: Hyaluronic acid possesses fungistatic activity but no candidacidal activity. HA showed inhibitory effects on the candidacidal activities of lysozyme and the peroxidase system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 33 publications
0
38
0
1
Order By: Relevance
“…This disappearance comes with the concomitant surface CE . During the healing period of the current study, postoperative discomfort was scored by patient self‐assessment using two aforementioned parameters, pain and burning sensation after exogenous use of HA, introduced as a practical means to enhance wound healing with unique physiochemical and biologic properties and, thus, quality of life …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disappearance comes with the concomitant surface CE . During the healing period of the current study, postoperative discomfort was scored by patient self‐assessment using two aforementioned parameters, pain and burning sensation after exogenous use of HA, introduced as a practical means to enhance wound healing with unique physiochemical and biologic properties and, thus, quality of life …”
Section: Discussionmentioning
confidence: 99%
“…Another major feature is viscoelasticity that provides stability and elasticity to tissues and delays penetration of viruses and bacteria . The highly biocompatible and non‐immunogenic nature of HA has bacteriostatic, fungistatic, anti‐inflammatory, antiedematous, osteoinductive, and proangiogenetic properties, leading to promotion of wound healing in a variety of tissues. Its properties have made HA of interest for treatment of various diseases in medical areas such as orthopedics, ophthalmology, and dermatology .…”
mentioning
confidence: 99%
“…Synergistic action of lysozyme with other salivary proteins has been suggested by several authors as a mechanism of action towards C. albicans , and some oral care products already combine lysozyme with lactoferrin and lactoperoxidase (2325). Indeed, in vitro investigations have shown that C. albicans susceptibility to lysozyme increases when combined with peroxidase (26,27) but not with lactoferrin (28), while hyaluronic acid inhibits the lysozyme effect on C. albicans (27,29). Lysozyme also enhances the activity of antimycotic drugs such as polyenes and azoles (3033).…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is commercially interesting mainly due to its antimicrobial activity, because it damages bacterial cell walls by catalyzing the hydrolysis of 1,4‐β‐bonds between GlcNAc and muramic acid . This enzyme has several applications in pharmaceutical, food and veterinary industries as fungistatic, anti‐inflammatory, antitumor, antiviral, a natural food preservative, etc . Therefore, the search for efficient and scalable strategies for its purification involves both an academic and an industrial challenge.…”
Section: Introductionmentioning
confidence: 99%